Establishment of a Novel Model for Anticancer Drug Resistance in Three-Dimensional Primary Culture of Tumor Microenvironment - Tatsuya Usui; Masashi Sakurai; Shuhei Enjoji; Hideyoshi Kawasaki; Koji Umata; Takashi Ohama; Nobuyuki Fujiwara; Ryotaro Yabe; Shunya Tsuji; Hideyuki Yamawaki; Shoichi Hazama; Hiroko Takenouchi; et al. (Stem Cells International)
Tumor microenvironment has been implicated in tumor development and progression. As a three-dimensional tumor microenvironment model, air liquid interface (ALI) organoid culture from oncogene transgenic mouse gastrointestinal tissues was recently produced. However, ALI organoid culture system from tissues of colorectal cancer patients has not been established. Here, we developed an ALI organoid model from normal and tumor colorectal tissues of human patients. Both organoids were successfully generated and showed cystic structures containing an epithelial layer and surrounding mesenchymal stromal cells. Structures of tumor organoids closely resembled primary tumor epithelium. Expression of an epithelial cell marker, E-cadherin, a goblet cell marker, MUC2, and a fibroblast marker, vimentin, but not a myofibroblast marker, α-smooth muscle actin (SMA), was observed in normal organoids. Expression of E-cadherin, MUC2, vimentin, and α-SMA was observed in tumor organoids. Expression of a cancer stem cell marker, LGR5 in tumor organoids, was higher than that in primary tumor tissues. Tumor organoids were more resistant to toxicity of 5-fluorouracil and Irinotecan than colorectal cancer cell lines, SW480, SW620, and HCT116. These findings indicate that ALI organoid culture from colorectal cancer patients may become a novel model that is useful for examining resistance to chemotherapy in tumor microenvironment.